Olhares sobre botânica: percepção botânica de estudantes de uma escola estadual de um município da região do Caparaó Capixaba - Lopes, Lucas da Rocha (2021)
Botany is the branch of Biology that studies plant organisms, from algae to plants with flowers and fruits in relation to their morphologies, physiologies, relationships with other living beings, including humans. Recent work indicates that people do not recognize or value plants, this phenomenon is called the Plant Awareness Disparity (PAD). This phenomenon is directly linked to the way people perceive plants, the botanical perception. What interferes with this botanical perception? What role does the school play in the formation of this perception? These questions lead us to the objective of this research was to investigate how is the perception of botany and the teaching of botany for students of Basic Education in a municipality in the Caparaó Capixaba region. Through the application of questionnaires for students in the 9th grade of elementary school, in the 3rd year of high school at the State School of Elementary and High School Jerônimo Monteiro. In addition, some of the students were selected to be interviewed. The questionnaires were designed based on the Likert Scale with five degrees of agreement. The content analysis technique was used to analyze the interviews, and to assist in the content analysis, Iramuteq software was used to perform the similarity analysis. The results found in this research are: the habits of the students seem to exert a great influence on the perception and recognition of plants in their daily lives and as elements present in the culture; the family has a great influence on the formation of interest and on the creation of habits of caring for plants; the school was not recognized as an agent of influence in the students' interest in relation to plants, being necessary that the school rethink the way the contents related to Botany are worked; although students recognize the existence of plants in their respective daily lives, they still show signs of PAD.